Post-fire mechanical properties of concrete made with recycled tire rubber as fine aggregate replacement. - Muhammad, Muhammad Arf; Abdullah, Wrya Abdulfaraj; Abdul-Kadir, Mohamed Raouf (Sulaimani Journal for Engineering Sciences, 2017)
In this study, effects of high blazing temperature with varied time durations on mechanical behavior of normal concrete containing recycled tire rubber as a fine aggregate (RTRFA) have been presented. RTRFA is used as a partial replacement of natural fine aggregate to make rubberized concrete. Generally, concrete used in structural members must satisfy fire resistance requirements in building codes. Therefore, this paper aims at studying the performance of the rubberized concrete prior and after its exposure to fire in accordance with ISO 834 curve for firing. It has been stipulated that the presence of tire rubber particles is mostly for the consideration of environment safeguard. In this investigation, five different concrete mixes were prepared with Ordinary Portland Cement, natural fine and coarse aggregate, with ﬁne aggregate replacement ratios (0%, 6%, 12%, 18% and 24%) by weight. From these mixes, 60 cylindrical specimens (100mm diameter × 200mm high) and 60 cubic specimens (150mm×150mm×150mm) were prepared. These concrete specimens were divided into four groups, consisting of 15 cubes and 15 cylinders each. The first group (so called “control”) were tested without exposing it to fire and the remaining three groups were separately subjected to fire for three different time periods vis. (20, 40 and 60 minutes) in a furnace fabricated according to ASTM E119. Then the concrete specimens were tested to observe the post-fire mechanical properties including split tensile strength, compressive strength and ultrasonic pulse velocity. The results of time-temperature curves, slump, fresh density, hardened density, percent-mass loss, compressive strength, split tensile strength of all the mixes are presented. The results showed that both the compressive strength and split tensile strength of concrete mixes decreased with higher percentage replacement of ﬁne aggregate by RTRFA before and after exposure to fire. Moreover, longer time of fire duration or higher replacement ratios leads to further strength reduction of compressive and split tensile strengths. Additionally, it was found that the usage of ultrasonic pulse velocity for concrete samples containing more than 6% of RTRFA as a replacement of sand gives unreasonable measurements. Finally, statistical equations were derived to predict these properties of concrete with RTRFA replacements.
Keywords: Fire; Rubberized concrete; Post-fire Mechanical properties; Recycled Tire Rubber Fine Aggregate (RTRFA)